Thin and ephemeral snow shapes melt and runoff dynamics in the Peruvian Andes - Catriona L. Fyffe; Emily Potter; Evan Miles; Thomas E. Shaw; Michael McCarthy; Andrew Orr; Edwin Loarte; Katy Medina; Simone Fatichi; Rob Hellström; Michel Baraer; Emilio Mateo; et al. (Communications Earth & Environment)
Abstract The snow and glaciers of the Peruvian Andes provide vital water supplies in a region facing water scarcity and substantial glacier change. However, there remains a lack of understanding of snow processes and quantification of the contribution of melt to runoff. Here we apply a distributed glacio-hydrological model over the Rio Santa basin to disentangle the role of the cryosphere in the Andean water cycle. Only at the highest elevations (>5000 m a.s.l.) is the snow cover continuous; at lower elevations, the snowpack is thin and ephemeral, with rapid cycles of snowfall and melt. Due to the large catchment area affected by ephemeral snow, its contribution to catchment inputs is substantial (23% and 38% in the wet and dry season, respectively). Ice melt is crucial in the mid-dry season (up to 44% of inputs). Our results improve estimates of water fluxes and call for further process-based modelling across the Andes.